2006
DOI: 10.1186/1742-6413-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: CytoJournal organized its first Peer-Reviewer's Retreat of 2006 during the United States and Canadian Academy of Pathology Annual Meeting at Atlanta on Feb 12, 2006. The major topics discussed were open access, peer review, and impact factors. Representative participants volunteered to join the task force to prepare an instructional guide for peer-reviewing cytopathology manuscripts. Concern about the impact factor for CytoJournal was discussed. A feedback to its readers and authors was recommended. Impact fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Eighty-one percent of all the citations in the reference list in the editorial were from Cytojournal articles and only 19% were from other journals. Similar trends can be observed in other editorials, letters to the editor and editor's replies [4]. These are examples of manipulation by self-citations or selective citations.…”
supporting
confidence: 48%
See 2 more Smart Citations
“…Eighty-one percent of all the citations in the reference list in the editorial were from Cytojournal articles and only 19% were from other journals. Similar trends can be observed in other editorials, letters to the editor and editor's replies [4]. These are examples of manipulation by self-citations or selective citations.…”
supporting
confidence: 48%
“…Clearly, this would have resulted in more citations for Cytojournal and thus increase IF; a quick scan of articles in previous issues showed that most of the cited articles were by Cytopathology Foundation members, the editors and editorial members of Cytojournal ! Although most of the original articles have citations that are not biased, the letters to the editor and the editor's replies were ‘loaded' with Cytojournal citations [1,4]. This is just one way that editors can maneuver a surge of the IF of their journal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their time and efforts for reviewing the manuscripts to improve their quality is commendable. A high standard of peer-review process in timely fashion is very important component of CytoJournal [27]. …”
Section: Editorialmentioning
confidence: 99%
“…″We as academicians strive to create wonderful sculptures in the form of published research in the hope of sharing it with all our colleagues and the general public.″3 No researcher would like that his/her article is not read due to monetary constraints of the reader to pay for journal access since that would restrict its readership to only a privileged few. ′Open access′ fulfills the ultimate goal of disseminating and sharing scholarly information.…”
mentioning
confidence: 99%